Myofibroblastic sarcoma of the oral cavity: a diagnostic dilemma and report of two cases - Ab Rahman Nurhayu; Harun Masitah Hayati; Sharif Sharifah Emilia Tuan (EDP Sciences, 2022)
Introduction: Myofibroblastic sarcoma is designated as a low-grade malignancy, commonly affecting the deep soft tissue of the head and neck. Despite being classified as low-grade, myofibroblastic sarcoma with high-grade features have been reported. Observations: Two such cases affecting the oral cavity, which were diagnosed as different entities upon biopsy, were observed. Case 1 presented as multiple, well-circumscribed soft tissue swellings of the tongue and alveolar mucosa and was diagnosed as synovial sarcoma. Case 2 manifested as a large extensive osseous lesion of the maxilla and was diagnosed as an inflammatory myofibroblastic tumour. Conclusion: Myofibroblastic sarcoma with high-grade features remains a diagnostic dilemma due to its overlapping features with other spectra of fibroblastic/myofibroblastic tumours and lack of consensus regarding its classification as a separate entity. Establishing the definitive diagnosis requires adequate tumour sampling and a systematic clinicopathological approach.